Detection of SARS-CoV-2 on surfaces in food retailers in Ontario - Maleeka Singh; Azin Sadat; Reihaneh Abdi; Louis A. Colaruotolo; Alyssa Francavilla; Katherine Petker; Pedram Nasr; Maryam Moraveji; Gyllian Cruz; Yinan Huang; Aditi Arora; Aleana Chao; et al. (Current Research in Food Science, 2021)
The COVID-19 pandemic has generated increased interest in potential transmission routes. In food retail settings, transmission from infected customers and workers and customers through surfaces has been deemed plausible. However, limited information exists on the presence and survival of SARS-CoV-2 on surfaces, particularly outside laboratory settings. Therefore, the purpose of this project was to assess the presence of the virus at commonly found surfaces at food retail stores and the potential role that these spaces play in virus transmission.Samples (n=957) were collected twice a week for a month in food-retail stores within Ontario, Canada. High-touch surfaces were identified and surveyed in 4 zones within the store (payment stations, deli counters, refrigerated food section and carts and baskets). The samples were analyzed using a molecular method, i.e., reverse transcriptase quantitative Polymerase Chain Reaction (RT-qPCR).Regardless of the store's location, the sampling day or time, the location of the surface within the store or the surface material, all samples tested negative for SARS-CoV-2. These results suggest that the risk of exposure from contaminated high-touch surfaces within a food retailer store is low if preventive measures and recommended sanitizing routines are maintained.